Analysis of von mises hypothesis usefulness for adhesive layer effort estimate - Godzimirski, Jan; Tkaczuk, Sławomir (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2019)
In the adhesive layer, uneven stress distribution and their complex state usually occur. Development of methodology for the analysis of adhesive layer was an aim of the experimental studies and numerical calculations. Specimens with adhesive layers which were similar to each other in terms of even distribution of stresses, were used in trials. This condition was met by using cylindrical oblique specimens consisting of two elements, obtained by cutting symmetrically at an angle of 45 ° a cylinder with a diameter of 12 mm and a height of 20 mm and bonding them adhesively on the cutting surfaces. The result of the experiment showed a greater than 2.26 to 2.92 strength of compressed specimens compared to stretched ones. It allows to conclude that the Mises hypothesis cannot be directly used for analysis of the state of stresses in adhesive joints. Numerical calculations were performed. For those, the model of the specimens was put under tension and compression with mean values of forces determined experimentally for specimens bonded with Epidian 57 adhesive. Conclusions were allowed to be formulate by conducted trials and calculations. Structural adhesives exhibit higher compressive strength rather than tensile strength. Consequently they exhibit indirect properties between metallic elastic plastics and brittle ceramic bodies. The criterion for destroying an adhesive bond loaded temporarily may be that the von Mises stress exceeds the absolute value of the tensile strength of the adhesive or compression. However it should be taken into account that those strengths have different values. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)